The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.bmcl.2009.03.134
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of thioether-bridged cyclic pentapeptides binding to Grb2-SH2 domain with high affinity

Abstract: Blocking the interaction between phosphotyrosine (pTyr)-containing activated receptors and the Src homology 2 (SH2) domain of the growth factor receptor-bound protein 2 (Grb 2) is considered to be an effective and non-cytotoxic strategy to develop new anti-proliferate agents due to its potential to shut down the Ras activation pathway. In this study, a series of phosphotyrosine containing cyclic pentapeptides were designed and synthesized based upon the phage library derived cyclopeptide, G1TE. A comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The specificity of the observed effect was confirmed by the lack of antiproliferative properties in MDA-MB-231 breast cancer cells that are independent of the Erb-B2 growth pathway. Subsequent optimization involved the replacement of the phosphonic acid by a malonate, which docks into the pY binding pocket. Alternative macrocyclic peptidic scaffolds devoid of the pY residue were recently reported as well …”
Section: Applications Of Synthetic Macrocycles In Drug Discoverymentioning
confidence: 99%
“…The specificity of the observed effect was confirmed by the lack of antiproliferative properties in MDA-MB-231 breast cancer cells that are independent of the Erb-B2 growth pathway. Subsequent optimization involved the replacement of the phosphonic acid by a malonate, which docks into the pY binding pocket. Alternative macrocyclic peptidic scaffolds devoid of the pY residue were recently reported as well …”
Section: Applications Of Synthetic Macrocycles In Drug Discoverymentioning
confidence: 99%
“…Several reports demonstrated that peptide-mediated interference in IAV polymerase complex assembly can attenuate IAV replication [53] [57] . SLiMs such as PDZ motif [58] , LIG_SH2_GRB2 [59] are being explored as drug targets. Since viruses have evolved to use motifs for essential functions by hijacking host proteins [60] , identification of SLiMs which mediate interactions between viral protein and host factors may provide valuable and specific information for development of motif mimetic drugs to perturb the interactions to treat virus infections [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Further, these peptides appeared to permeate the cell membrane and phosphorylation of Her2 was found to be downregulated after treating whole cells with the Grb2 macrocycle antagonists. Multiple variations of cyclized Grb2 inhibitors were later developed with the installment of C-terminal β-functionalized allylglycines for ring-closing metathesis (RCM) (Oishi, et al, 2005), azide-alkyne cycloaddition macrocycles (Choi, et al, 2006), thioether-bridged macrocyclization (Jiang, et al, 2009) and peptide bicycles containing both head-to-tail and side chain cyclization (Quartararo, Wu, & Kritzer, 2012). Many of these peptides demonstrated improved properties including increased affinity, improved inhibition and enhanced proteolytic stability.…”
Section: Constrained Peptides As Disruptors Of Kinase-mediated Promentioning
confidence: 99%